Analisis Efektivitas Program Asimilasi Terhadap Narapidana Kelas II A Banda Aceh Pada Masa Pandemi Covid 19 Tahun 2020 - Arif Fonna; Iqbal Ahmady (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
In the context of overcoming and preventing Covid-19 through Regulation of the Minister of Law and Human Rights (PERMENKUMHAM) Number 10 of 2020 concerning the conditions for granting assimilation and integration rights for prisoners and children in the context of preventing and overcoming the spread of Covid-19. This creates unrest among the public, this unrest creates fear in the community so that there are those who claim that the assimilation program is just a government game given the occurrence of overloaded prisons/detention centers, which the government should have done to increase the capacity of prisons/detention centers to maintain the increase in the spread of the virus. This study aims to find out and explain about the guidance and supervision carried out by the Fathers for Class II A prisoners in Banda Aceh as well as to find out and explain the effectiveness of the assimilation program for Class II A prisoners in Banda Aceh during the Covid-19 pandemic in 2020. The research approach carried out using descriptive qualitative method. The results of this study indicate that there are several forms of guidance and supervision of inmates, namely: (1) the supervision of the Fathers through Zoom Meetings, and (2) the supervision of the Fathers through the Family/Village Apparatus. And the effectiveness of the convict assimilation program at the Class II A prison in Banda Aceh during the COVID-19 pandemic in 2020 in the context of overcoming and preventing the virus is somewhat less effectie given the absence of direct guidance and supervision of prisoners receiving the assimilation program.The conclusion is the form of guidance and supervision carried out by the Fathers for Class II A Banda Aceh prisoners, namely, collaborating with the family and related village officials in controlling the behavior of prisoners and the supervision provided, namely, making Video Calls or Zoom Meetings which are routinely carried out every day. by showing the face directly. The experimental approach is the most likely approach in terms of the effectiveness of the assimilation program for Class II A prisoners in Banda Aceh in 2020.